IMPLANTATION OF THE PERMANENT PACEMAKER; FROM SUPERIOR VENA CAVA IN A PATIENT WITH FIBROSIS OF BOTH SUBCLAVIAN VEINS - Shah, Bakhtawar; Khan, Bahauddin; Saidullah, Shahab (Journal of Ayub Medical College Abbottabad, 2021)
Overall life span has increased with improved management of cardiac diseases all over the world which has opened the door of degenerative cardiac diseases. On the other hand, stat of the art corrective congenital cardiac disease also increased the volume of adult living with treated congenital heart diseases. Both these factors lead to a new epidemic in cardiology of complete heart block (CHB). Permanent pacemakers (PPM) implantation is a life-saving procedure for CHB. Permanent pacemakers are usually implanted from upper limb veins. But at time upper limb veins are not suitable for implantation due to various anatomical and pathological reasons, so alternative methods are used for implantation of devices. We are reporting a case of PPM implantation from Superior Vena Cava (SVC).